REFLEKSI GENDER DALAM PEMBELAJARAN KURIKULUM 2013; STUDI TERHADAP HASIL BELAJAR IPS SISWA KELAS MODEL DI SOLOK, SUMATERA BARAT - Habibullah Habibullah (Kafa`ah: Journal of Gender Studies, 2014)
This article tries to reveal that learning process of 2013 curriculum give Junior High School Students a good perception on concept of space and time connectivity, and social activity which has gender phenomena. Thus gender perception can be observed by learning output of social science in cognitive domain on students in model class at Junior High School 1 of Gunung Talang. The research says that learning output shows female students’ cognitive competence dominate male students’.  This  statement  also proves  that  common stereotype that is usually labeled to male students is also socially labeled toward female students. Keywords:  social  science  learning  output,  model  class,  gender reflection, curriculumCopyright © 2014 by Kafa`ah All right reservedDOI : 10.15548/jk.v4i2.100